Principals' Digital Leadership Strategies in Improving Teacher Performance through Digital Supervision: A Phenomenological Qualitative Study - Rita Prima Bendriyanti; Citra Dewi; Suwarni Suwarni (Universitas Trunodjoyo Madura, 2025)
The digital transformation in education demands a paradigm shift in principal leadership, particularly in the implementation of teacher performance supervision. Conventional, administrative supervision is considered insufficiently adaptive to the demands of digital learning. This situation necessitates an in-depth study of principals' digital leadership strategies for improving teacher performance through digital supervision. This study aims to examine and understand in depth the digital leadership strategies of school principals in improving teacher performance through digital supervision based on the experiences of educational practitioners. This study employed a qualitative approach with a phenomenological design. Participants included school principals and teachers directly involved in digital supervision. Data were collected through in-depth interviews, observations, and documentation studies, then analyzed using phenomenological analysis to identify essential themes. The research results show that principals' digital leadership is realized through digital data-based supervision planning, collaborative supervision implementation, and ongoing reflective follow-up. These strategies have resulted in improved teacher performance in aspects of lesson planning, pedagogical reflection, and technology-based learning innovation. This study concludes that principals' digital leadership plays a strategic role in building an adaptive and sustainable professional supervision culture. The research's novelty lies in uncovering the subjective experiences of principals and teachers in digital supervision, positioning technology as an instrument of reflective leadership, not merely an administrative tool.